Ephemeral Content Domination: How to Harness the Power of Stories - Miko Andi Wardana; Fatimah Abdillah; Nurlela Nurlela (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research article examines the factors contributing to domination in ephemeral content for PT. Tirta Investama, focusing on the roles of creativity of content, frequency of posting, and engagement level. Using a quantitative research design and a sample of 100 consumers, the study explores both direct and indirect effects among these variables, utilizing path analysis with Smart PLS. The findings reveal that both creativity and frequency of posting have significant direct effects on engagement level and domination in ephemeral content. Additionally, engagement level serves as a critical mediator, linking creativity and frequency of posting to domination in ephemeral content. The results suggest that for PT. Tirta Investama to achieve a dominant position in the ephemeral content space, the company must prioritize creative, high-quality content and maintain a consistent posting schedule to drive audience engagement. The indirect effects highlight the importance of engagement as a conduit between content strategies and overall brand influence. These insights offer valuable guidance for PT. Tirta Investama's digital marketing strategy, emphasizing a balanced approach to content creation and audience interaction for long-term success in the ephemeral content landscape.